Deteksi Radiologis Dini Osteoartritis Genu sebagai Upaya Preventif dalam Menurunkan Risiko Disabilitas - Tjie Haming Setiadi; Santoso, Alexander Halim; Dwiana, Alya; Jeffrey Jeffrey; Limanan, David (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Knee osteoarthritis (OA) is one of the leading causes of disability among the elderly population. This degenerative joint disease is characterized by progressive damage to the articular cartilage and structural alterations of the knee joint, resulting in pain, reduced mobility, and diminished quality of life. This Community Service Program (PKM) aimed to promote early detection of knee OA through simple radiological screening as a preventive strategy to reduce the risk of musculoskeletal disability. The activity was conducted at Asisi Church, South Jakarta, involving 87 participants aged 54–87 years (mean 70.77 ± 7.32 years). Radiological examination was performed using standard anteroposterior knee X-rays, and results were classified according to the Kellgren–Lawrence grading system. Findings revealed that 98.9% of participants exhibited radiological signs of OA, predominantly grade II (60.9%), followed by grade III (21.8%), grade I (11.5%), and grade IV (4.6%), while only 1.1% showed normal results. Female participants (74.7%) predominated across all OA grades, indicating hormonal and biomechanical influences on disease progression. The mean age increased with OA severity, supporting the degenerative theory that aging leads to decreased chondrocyte function and cartilage elasticity. In addition to screening, participants received education on weight management, muscle strengthening exercises, and injury prevention. The results demonstrate that simple radiological screening is an effective, practical, and cost-efficient community-based approach for early detection of knee OA. Integrating such preventive strategies within primary care systems could significantly reduce the burden of disability among the elderly population.